The Role of MDCT Coronary Angiography in the Detection of Benign Varieties and Anomalies of Coronary Blood Vessels—A Narrative Review - Ana Mladenovic Markovic; Ana Tomic; Miodrag Nisevic; Biljana Parapid; Nikola Boskovic; Marina Vitas; Miona Jevtovic; Sandra Grujicic (Medicina)
Coronary arteries may vary in quantity, point of origin, or course. These variations fall under the category of anatomical variants/anomalies of the coronary arteries, representing congenital abnormalities of the coronary vascular system. Generally, they are benign, asymptomatic, and identified inadvertently during coronary angiography conducted for alternative indications. However, in some cases, the anomaly’s characteristics or its interaction with surrounding structures may cause hemodynamic disturbances. These disturbances can lead to turbulent blood flow, which in turn poses an increased likelihood for the development of atherosclerosis and myocardial ischemia. If symptomatic, potential manifestations include chest pain, arrhythmias, syncope, myocardial infarction, and sudden cardiac death. Given the potential for life-threatening complications in certain cases, the early and accurate diagnosis of coronary artery anomalies is of paramount importance. The most common diagnostic procedures used for the evaluation of coronary vessels are coronary angiography and multi-detector row computed tomography (MDCT) coronary angiography. MDCT angiography is a non-invasive, dependable, safe, and sensitive method for the detailed visualization of coronary anatomy. It offers high-resolution imaging that enables precise assessment of congenital coronary variations, aiding in both clinical decision-making and long-term patient management. We conducted a narrative review to analyze and integrate the body of literature on coronary artery varieties and anomalies. Our objective was to provide a comprehensive, albeit non-exhaustive, overview of essential concepts and findings related to their definition, classification, and detection with MDCT angiography. By integrating current knowledge in MDCT imaging, we seek to contribute to a better understanding of the clinical implications of coronary artery variations and their role in cardiovascular health.